Analysis of Determinants of Consumer Intention to Use Online Car Loan Services in Indonesia - Wilson Darma Setiawan; Yokie Radnan (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
This study examines the determinants of consumer intention to use online car loan services in Indonesia, focusing on the application of the Theory of Perceived Risk (TPR). As digital financial services continue to grow rapidly in Indonesia, understanding the factors influencing consumer adoption of online car loans becomes crucial. Using a quantitative approach, this research surveyed 400 potential users of online car loan services in major Indonesian cities. The study investigates six dimensions of perceived risk: financial, security, performance, privacy, time, and social risks. Results indicate that security and privacy risks are the most significant factors negatively affecting consumer intention, while perceived benefits and ease of use positively influence adoption intention. Notably, cultural and social factors unique to the Indonesian context also play a substantial role in shaping consumer behavior. These findings contribute to the growing body of literature on fintech adoption in developing countries and provide practical insights for online car loan service providers and regulators in Indonesia. The study suggests strategies for mitigating perceived risks and enhancing consumer trust to promote the adoption of online car loan services.